Brittle mechanical behavior and damage constitutive model of deep mylonite under the high geo-stress state - Peng, Guoping; Lin, Wei; Zhao, Mengdi (Frontiers in Earth Science, 2025)
IntroductionDuring the excavation of deep underground engineering, stress redistribution in rock mass often leads to obvious stress-deformation failure characteristics. It is important to study the stress-strain characteristics of rock for the safety construction and protection of underground engineering.MethodsBased on rock basic density test, rock and mineral microscopic test and triaxial compression test, brittle deformation failure mechanical characteristics of a deep mylonite under high in-situ stress state are obtained. A rock damage constitutive model is established and compared with triaxial test results. Finally, the physical significance of model parameter (a) and parameter (r) is analyzed.ResultsMylonite exhibits obvious brittle mechanical characteristics under high stress state, and the established rock damage constitutive model can well describe this brittle deformation characteristic. The damage degree increases from 0 to 1 gradually, and the damage rate increases first and then decreases.DiscussionThe effects of parameters a and r on the constitutive model and damage degree are discussed. Parameter A mainly affects the peak strength of the model, the brittleness of the rock, and the extreme point strain that affects the degree of damage. Parameter r mainly affects the peak strength of the model, and the extreme point damage degree is affected. In addition, the concept of brittleness index is introduced and its engineering applications are explored.